2012
DOI: 10.1007/s10896-012-9440-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Intimate Partner Violence Against Women in Marivan County, Iran

Abstract: This paper reports on the prevalence of intimate partner violence (IPV) as well as individual, socioeconomic, and family function characteristics associated with IPV among women attending public health services in Marivan County, Iran. Multistage cluster sampling was employed to recruit 770 women to participate in the study. This descriptive, cross-sectional study took place from May to November 2009. The majority of the women (79.7 %) had experienced psychological IPV, followed by physical IPV (60 %) and sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Iranian women are more likely to experience the verbal and psychological abuse (Abadi et al 2012). Likewise, Nouri et al (2012) reported that the majority of the women (79.7%) have experienced psychological IPV, followed by physical IPV (60%), and sexual IPV (32.9%) in Marivan City, Iran.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Iranian women are more likely to experience the verbal and psychological abuse (Abadi et al 2012). Likewise, Nouri et al (2012) reported that the majority of the women (79.7%) have experienced psychological IPV, followed by physical IPV (60%), and sexual IPV (32.9%) in Marivan City, Iran.…”
Section: Introductionmentioning
confidence: 98%
“…To understand the seriousness of this problem, it must be considered that the female population constitutes 49.7% of the total population in Iran (The World Bank 2017), so the consequences of this violence affect the whole society. In addition, the results of quantitative research shows that domestic violence has increased in Iran (Vakili et al 2010;Nouri et al 2012). According to a national survey carried out on IPV against women, in 28 provinces of Iran, at least one act of serious physical violence was reported by 66% of married women.…”
Section: Introductionmentioning
confidence: 99%
“…23 As for the nature of violent actions, high percentages were also identified in Iran, where 79.7% of women were victims of intimate partner violence, 60.0% intimate partner violence, and 32.9% intimate partner violence sexual. 42 In Sweden, the prevalence of intimate partner violence against women was lower than in most publications: 25.0% psychological, 7.5% physical and 2.8% sexual. 20 Although it is often neglected by women's protection services and by health professionals, psychological aggression deserves attention, since it is usually the first form of violence in the context of a chain that can reach its peak, femicide.…”
Section: /17mentioning
confidence: 80%
“…Intimate Partner Violence has been identified as a significant public health problem [Nouri et al, 2012]. It is a social and health problem in all societies and cultures all over the globe [Al-Badayneh, 2012].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Partner violence has been socially constructed as a predominantly masculine deviance, whereby male use their power and control gained through socialization to dominate women [Bailey, Eistikovits and Buchibinder, 2012]. It is the use of actual or threatened physical, sexual and psychological violence by a current partner [Nouri et al 2012].…”
Section: Introductionmentioning
confidence: 99%